CAKUPAN ANC DAN CAKUPAN TABLET FE HUBUNGANNYA DENGAN PREVALENSI ANEMIA DI JAWA TIMUR - Sylvi Natalia; Sri Sumarmi; Siti Rahayu Nadhiroh (Media Gizi Indonesia, 2016)
Iron supplementation is one of the anemia prevention program in Indonesia. Success Indicator of its program is ANC coverage and coverage of iron tablet distribution. This study aimed to analyze the relationship between the ANC (Antenatal Care) and iron tablet coverage with prevalence of anemia among pregnant women in East Java year 2015. This research used data report from Nutrition Division and Family Health Division of Provincial Health Office East Java. Data was analyse using Pearson correlation test. The prevalence of anemia among pregnant women in East Java was 5.8%, the result are still below the national target which is 28%. The result showed that there was no relationship between the ANC and iron tablet coverage with the prevalence of anemia (p-value > 0.05). It is concluded that coverage of iron supplementation among pregnant women through ANC does not describe the prevalence of anemia among pregnant women due to many factors that infl uence anemia such as bioavailability of iron and compliance pregnant women consume iron.Keywords: anemia, ANC coverage, iron tablet